Community structure analysis of endoparasitic helminths of Anabas testudineus from unpolluted and polluted sites of a freshwater body of Dhaka - Ghani, Md Osman; Bhuiyan, Aminul Islam; Bushra, Jannatul (Dhaka University Journal of Biological Sciences, 2014)
Community structure of metazoan endoparasites of Anabas testudineus collected from an unpolluted and a polluted water body was determined. Out of 100 A. testudineus observed, 78% was parasitized by at least one species of endohelminth parasite. Eight metazoan endoparasites were recorded. Nematode showed higher prevalence than trematode. One species was accounted as satellite species and others as secondary. Larger hosts were more abundantly infected than the smaller ones as positive correlation was observed between the standard length of the hosts and the abundance/ prevalence of all parasites. Maximum parasite species followed a typical overdispersed type of distribution pattern. Parasite species richness was lower in fish from polluted (4) than unpolluted water (6). Per cent similarity of infestation between the sample hosts was high (55.73%). Three common parasite species from both sample hosts showed insignificant difference in intensity of infestation in relation to host habitat. Host sex had influenced infestation at infra?community but not at component community level. Interspecies association between parasites was strong in fish from unpolluted in comparision from polluted water. Hosts habitat quality also played an influential role in building parasite community, diversity and other associated community indices. DOI: http://dx.doi.org/10.3329/dujbs.v23i1.19823 Dhaka Univ. J. Biol. Sci. 23(1): 27-38, 2014